Effects of TP53 mutational status on gene expression patterns across 10 human cancer types. Issue 5 (29th January 2014) - Parikh, Neha; Hilsenbeck, Susan; Creighton, Chad J; Dayaram, Tajhal; Shuck, Ryan; Shinbrot, Eve; Xi, Liu; Gibbs, Richard A; Wheeler, David A; Donehower, Lawrence A
Abstract Mutations in the TP53 tumour suppressor gene occur in half of all human cancers, indicating its critical importance in inhibiting cancer development. Despite extensive studies, the mechanisms by which mutant p53 enhances tumour progression remain only partially understood. Here, using data from the Cancer Genome Atlas (TCGA), genomic and transcriptomic analyses were performed on 2256 tumours from 10 human cancer types. We show that tumours with TP53 mutations have altered gene expression profiles compared to tumours retaining two wild‐type TP53 alleles. Among 113 known p53‐up‐regulated target genes identified from cell culture assays, 10 were consistently up‐regulated in at least eight of 10 cancer types that retain both copies of wild‐type TP53. RPS27L, CDKN1A (p21CIP1) and ZMAT3 were significantly up‐regulated in all 10 cancer types retaining wild‐type TP53. Using this p53‐based expression analysis as a discovery tool, we used cell‐based assays to identify five novel p53 target genes from genes consistently up‐regulated in wild‐type p53 cancers. Global gene expression analyses revealed that cell cycle regulatory genes and transcription factors E2F1, MYBL2 and FOXM1 were disproportionately up‐regulated in many TP53 mutant cancer types. Finally, > 93% of tumours with a TP53 mutation exhibited greatly reduced wild‐type p53 messenger expression, due to loss of heterozygosity or copy neutral loss of heterozygosity, supporting the concept of p53 as a recessive tumour suppressor. The data indicate that tumours with wild‐type TP53 retain some aspects of p53‐mediated growth inhibitory signalling through activation of p53 target genes and suppression of cell cycle regulatory genes. Published by John Wiley & Sons, Ltd. www.pathsoc.org.uk